2021
DOI: 10.1093/gbe/evab262
|View full text |Cite
|
Sign up to set email alerts
|

The Tetragnatha kauaiensis Genome Sheds Light on the Origins of Genomic Novelty in Spiders

Abstract: Spiders (Araneae) have a diverse spectrum of morphologies, behaviours and physiologies. Attempts to understand the genomic-basis of this diversity are often hindered by their large, heterozygous and AT-rich genomes with high repeat content resulting in highly fragmented, poor-quality assemblies. As a result, the key attributes of spider genomes, including gene family evolution, repeat content, and gene function, remain poorly understood. Here, we used Illumina and Dovetail Chicago technologies to sequence the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 87 publications
1
18
0
Order By: Relevance
“…The copyright holder for this preprint this version posted December 2, 2022. ; https://doi.org/10.1101/2022.11.29.518358 doi: bioRxiv preprint gene annotations of the T. kauaiensis genome (Cerca et al 2021a). We then called orthologs between T. kauaiensis and the Drosophila melanogaster genome annotations to obtain evidence on gene function, benefiting from the decades of functional genetic research on the latter, using OrthoFinder2 (Emms and Kelly 2015).…”
Section: Scans Of Selectionmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted December 2, 2022. ; https://doi.org/10.1101/2022.11.29.518358 doi: bioRxiv preprint gene annotations of the T. kauaiensis genome (Cerca et al 2021a). We then called orthologs between T. kauaiensis and the Drosophila melanogaster genome annotations to obtain evidence on gene function, benefiting from the decades of functional genetic research on the latter, using OrthoFinder2 (Emms and Kelly 2015).…”
Section: Scans Of Selectionmentioning
confidence: 99%
“…Comparative arachnid genomics is just taking flight given the diversity of arachnid karyotypes (Kraĺ et al, 2019) and genome sizes [Table 1; see also (Cerca et al, 2021)]: these range from the smallest known arthropod genome at 90 megabases (Mbp) in the mite Tetranychus urticae (Grbićet al, 2011) to a sizeable 4.29 gigabases (Gb) in the velvet spider Stegodyphus dumicola (Liu et al, 2019). The currently limited number of arachnid genomes reveal high rates of methylation in spiders and scorpions, perhaps suggesting epigenetic control of large portions of arachnid genes (Thomas et al, 2020).…”
Section: Grand Challenge 3: Interpret Arachnid Trait Evolution Throug...mentioning
confidence: 99%
“…Gene duplication acts as a primary mode of evolutionary diversification by providing new genetic material that serves as a reservoir for subfunctionalization and neofunctionalization under selective pressure (Ohno 2013;Sémon and Wolfe 2007;Zhang 2003). In previous studies in spiders, evidence of whole genome duplication has been reported, including the presence of multiple copies of Hox genes (Sheffer et al 2021;Cerca et al 2021;Clarke et al 2015Clarke et al , 2014 and the expansion of silk genes and chemosensory genes (Cerca et al 2021). We analyzed the U. diversus genome to identify signatures of whole genome duplication.…”
Section: Whole Genome Duplicationmentioning
confidence: 99%
“…Spider genomes are enormous with high repeat content, making them challenging to assemble(Sanggaard et al 2014; Stellwagen and Renberg 2019; Ayoub et al 2013). While 22 spider genomes have been assembled and made publicly available(Sanggaard et al 2014; Babb et al 2017; Kono et al 2019; Sheffer et al 2021; Sánchez-Herrero et al 2019; Schwager et al 2017; Fan et al 2021; Yu et al 2019; Liu et al 2019; Escuer et al 2022; Cerca et al 2021; Zhu et al 2022; Hendrickx et al 2022; Kono et al 2021a; Purcell and Pruitt 2019; Li et al 2022; Kono et al 2021b) ( Table S1 ), most are highly fragmented, with 6 assembled to chromosome-scale(Sheffer et al 2021; Fan et al 2021; Escuer et al 2022; Zhu et al 2022; Hendrickx et al 2022; Kono et al 2021b). Of the 22 genomes, only 7 represent the Araneoidea(Kono et al 2019; Sheffer et al 2021; Fan et al 2021; Kono et al 2021a) or ecribellate orb-weavers, 2 of which have been assembled to chromosome-scale(Sheffer et al 2021; Fan et al 2021).…”
Section: Introductionmentioning
confidence: 99%